KEPEMIMPINAN PEREMPUAN DALAM ISLAM - Haris, Munawir (Analisis: Jurnal Studi Keislaman, 2015)
THE LEADERSHIP OF WOMEN IN ISLAM: The role of women in a religious society  to the question  of who and what  women are, the answer to which is found in the Koran. In these sacred Islamic verses the role and nature of women have been described by Allah, the almighty  creator  of us all. Despite  the traditional multi-ethnicity   of   Ismaic   tradition    society’s  social   fabric, however, Islam as a universal religion for the entire country has shaped the structure  of Islam’s society  and the mentality  of its citizens.  Within  the Islamic religious belief and the Koran, the belief is that  women were created for the main purpose of their husbands.  In fact,  the Islam is universal  religion.  This  articale analisise  about  existence  woman in the  leadership  in Islam  as universal religion.